2005
DOI: 10.1038/nmat1309
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly inherent voltage-controlled conductance switching

Abstract: Molecular electronics has been proposed as a pathway for high-density nanoelectronic devices. This pathway involves the development of a molecular memory device based on reversible switching of a molecule between two conducting states in response to a trigger, such as an applied voltage. Here we demonstrate that voltage-triggered switching is indeed a molecular phenomenon by carrying out studies on the same molecule using three different experimental configurations-scanning tunnelling microscopy, crossed-wire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
305
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(324 citation statements)
references
References 26 publications
16
305
2
1
Order By: Relevance
“…Such statistical consideration is essential in molecular electronics where the flexible nature of molecules and the indeterminacy of molecule-electrode interfaces significantly hamper the identification of a truly molecular switching signal. 11 For each GSCC and MSCC configuration, we carried out two independent MD simulations and from each run we selected four random configurations at the 10 ps time interval to prepare eight molecular structures. As shown in Figs Before discussing Fig.…”
Section: ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation
“…Such statistical consideration is essential in molecular electronics where the flexible nature of molecules and the indeterminacy of molecule-electrode interfaces significantly hamper the identification of a truly molecular switching signal. 11 For each GSCC and MSCC configuration, we carried out two independent MD simulations and from each run we selected four random configurations at the 10 ps time interval to prepare eight molecular structures. As shown in Figs Before discussing Fig.…”
Section: ͑1͒mentioning
confidence: 99%
“…While the voltage-gated conformational change of the molecules between the off-state GSCC and the on-state MSCC was proposed as the switching mechanism, 3-6 the molecular origin of the switching was questioned 7 as seemingly contradictory experiments appeared. [8][9][10] Indeed, differentiating a molecularly inherent switching from a stochastic one is a difficult task, 11 because the charge transport in molecular scale junctions is strongly influenced by the moleculeelectrode contacts and conformational fluctuations of molecules. [12][13][14][15] In a recent work, 16 employing realistic catenane monolayer models sandwiched between Au͑111͒ electrodes , we explicitly showed that the electrical switching ͑between on and off͒ can originate from the energetic movement of frontier orbitals that accompanies the structural switching of the molecule ͑between GSCC and MSCC, respectively͒.…”
mentioning
confidence: 99%
“…The molecular-based devices possess unique advantages for electronic applications, [3] such as lower cost, lower power dissipation, higher efficiency, ability of self-assembly and recognition, distinct optical and electronic properties, and synthetic tailoring ability by elaborate choice of geometry and composition. A variety of specific electronic functions performed by single molecules, including rectifiers, [4,5] switches [6,7] and transistors, [8][9][10] have been accordingly designed and reported. All the above aspects render molecules as ideal candidates for the next generation of electronics.…”
Section: Introductionmentioning
confidence: 99%
“…[6] All devices manufactured by this kind of method can be categorized as 'prototype devices', which are very useful for fundamental investigations and have already provided many important results. [4][5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, these devices are far from practical applications, as we can not imagine a nanometer device carrying a huge scanning probe microscopy (SPM) system or other systems. The other way utilizes nanogap electrodes [28][29][30][31][32] to form metal/molecule/metal devices.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments have also revealed a wealth of interesting transport phenomena including Coulomb blockade, 13 Kondo effect, 29 negative differential resistance, 26,30,31 switching, and hysteresis. [32][33][34] Furthermore, the possibility to obtain transport characteristics that resemble those of a diode 20 or a transistor 11 has been demonstrated. These findings have stimulated great interest in the basic mechanisms which govern quantum transport at the molecular scale.…”
Section: Introductionmentioning
confidence: 99%